Revisiting the Genetic Ancestry of Brazilians Using Autosomal AIM-Indels - Saloum de Neves Manta, Fernanda; Pereira, Rui; Vianna, Romulo; Rodolfo Beuttenmüller de Araújo, Alfredo; Leite Góes Gitaí, Daniel; Aparecida da Silva, Dayse; de Vargas Wolfgramm, Eldamária; da Mota Pontes, Isabel; Ivan Aguiar, José; Ozório Moraes, Milton; Fagundes de Carvalho, Elizeu; Gusmão, Leonor (PLOS ONE, 2013)
There are many different studies that contribute to the global picture of the ethnic heterogeneity in Brazilian populations. These studies use different types of genetic markers and are focused on the comparison of populations at different levels. In some of them, each geographical region is treated as a single homogeneous population, whereas other studies create different subdivisions: political (e.g., pooling populations by State), demographic (e.g., urban and rural), or ethnic (e.g., culture, self-declaration, or skin colour). In this study, we performed an enhanced reassessment of the genetic ancestry of 1,300 Brazilians characterised for 46 autosomal Ancestry Informative Markers (AIMs). In addition, 798 individuals from twelve Brazilian populations representing the five geographical macro-regions of Brazil were newly genotyped, including a Native American community and a rural Amazonian community. Following an increasing North to South gradient, European ancestry was the most prevalent in all urban populations (with values up to 74%). The populations in the North consisted of a significant proportion of Native American ancestry that was about two times higher than the African contribution. Conversely, in the Northeast, Center-West and Southeast, African ancestry was the second most prevalent. At an intrapopulation level, all urban populations were highly admixed, and most of the variation in ancestry proportions was observed between individuals within each population rather than among population. Nevertheless, individuals with a high proportion of Native American ancestry are only found in the samples from Terena and Santa Isabel. Our results allowed us to further refine the genetic landscape of Brazilians while establishing the basis for the effective application of an autosomal AIM panel in forensic casework and clinical association studies within the highly admixed Brazilian populations.